1991
DOI: 10.1111/j.1748-1716.1991.tb09181.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial blood flow and lactate metabolism at rest and during exercise with reduced arterial oxygen content

Abstract: The effect of a reduction in arterial oxygen content, equivalent to acute exposure to an altitude of 2300 metres above sea level, on myocardial blood flow and oxygen and lactate exchange was studied by coronary sinus catheterization in 12 healthy men. Measurements were made at rest, during atrial pacing and during submaximal and maximal exercise both breathing air and breathing 15% oxygen (hypoxia). Coronary sinus blood flow was measured by thermodilution and the possibility of a simultaneous uptake and releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 15 publications
2
15
1
Order By: Relevance
“…In the present study the myocardial perfusion values were found to be slightly higher than in some other studies (10,11). One possible explanation could be methodological differences between studies.…”
Section: Discussionsupporting
confidence: 36%
See 2 more Smart Citations
“…In the present study the myocardial perfusion values were found to be slightly higher than in some other studies (10,11). One possible explanation could be methodological differences between studies.…”
Section: Discussionsupporting
confidence: 36%
“…In humans, Grubbstrom et al (10) found with coronary sinus catheterization and thermodilution measurement that maximal coronary blood flow was 3.5-fold higher than at rest in sedentary subjects, although further increase was observed when maximal exercise was performed during hypoxia (10). However, by extrapolating from the results of the present study peak myocardial perfusion in humans would be ϳ5 ml⅐g Ϫ1 ⅐min Ϫ1 (ϳ7-fold higher than resting myocardial perfusion), assuming that the relationship between myocardial perfusion and workload remains linear (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed coronary flow reserve exists during maximal exercise in hypoxia, confirming the absence of myocardial hypoxia (7,8). These data prove 1) that cardiac function during exercise in hypoxia is not regulated to maximize blood flow to the exercising limbs and 2) that the progressively lower cardiac outputs during maximal exercise with increasing hypoxia cannot be due to myocardial failure.…”
Section: Viewpointmentioning
confidence: 52%
“…During maximal exercise the compensatory mechanism is an increase in coronary , heart rate (f c ) and stroke volume (SV) at a given oxygen uptake ( _ V O 2 ). See text for the results of the regression analysis blood¯ow, indicating that a normal heart has à`c oronary¯ow reserve'' that can be used in hypoxia (Grubbstrom et al 1991;Kaijser et al 1990). As the increase in¯ow is accompanied by an increase in coronary arterial pressure and stiness (Templeton et al 1972), the stiening of the ventricle could shift the enddiastolic pressure (EDP)/end-diastolic volume (EDV) curve to the left (Janicki et al 1996).…”
Section: Cardiovascular Limitationmentioning
confidence: 98%